CHANGES IN THE PHYSICAL PERFORMANCE OF HIGHLY QUALIFIED BASKETBALL PLAYERS DURING TRAINING UNDER THE INFLUENCE OF VARIOUS LOADS - Farxod Azadovich Pulatov (Proximus Journal Publishing, 2024)
The analysis of results of the research of the level of development of special efficiency of young basketball players of 18-19 years and the possibility of its preservation in the course of the game is presented in article. It is established that such level of the studied qualities decreases in process of end of game parties more and more. The opinion is put forward that such dynamics of change of these qualities demonstrates instability of their status
Keywords: basketball players; special working capacity; hopping endurance